Nano‐Biomedicine based on Liquid Metal Particles and Allied Materials. Issue 4 (8th February 2021) - Sun, Xuyang; Yuan, Bo; Wang, Hongzhang; Fan, Linlin; Duan, Minghui; Wang, Xuelin; Guo, Rui; Liu, Jing
Abstract : Liquid metals (LMs) have emerged as a new class of functional materials with attractive characteristics of low melting points and metal properties. Remarkable features, such as biocompatibility, injectability, plasticity, conductivity, and shape transformability, have rendered them as excellent candidates to tackle challenging biomedical issues, such as tumor clinics, tissue engineering, and even nerve connection. Scaling down the droplet size offers more opportunities in surface engineering and functionalization, thus providing broad biomedical scenarios expanding from drug delivery, enhanced bioheat transfer, tumor therapeutics, and bioelectronics to nanorobots. Despite in its infancy stage, a summary about the advancement of LM biomedical nanomaterials is urgently needed. This review aims to highlight the advantages of gallium‐based LM nanoparticles enabled nano‐biomedicine, to summarize the recent synthesis methods with diverse LM compositions, structures and surface modifications, and to introduce their typical state‐of‐the‐art biomedical applications. Challenges and opportunities are also discussed in the end. Abstract : The advantages of the liquid metal nanoparticles, including the oxide layer enabled core‐shell structure, biosafety, biodegradability and stimuli‐responsive properties, distinguish them from those solid counterparts. This review is dedicated to highlight the merits of gallium‐based nanoparticles enabled nano‐biomedicine, outlining the scenario of gallium‐based nanoparticles for biomedicine.